The Idea of Sustainable Development in Reflection on the Meaning of Knowledge and Cognition - Klimska, Agnieszka (Problemy Ekorozwoju, 2020)
In the case of philosophical justifications of sustainable development it is important to work out epistemological standpoints, adequate to the problems considered in the areas of particular development concepts based on speculative, theoretical knowledge as well as on practical one related to activity and serving its purposes. Epistemology must correlate with the problems that are their material object as well as with goals and cognitive and practical tasks that they (concepts) have to deal with. The present article makes an attempt at presenting reflection on knowledge and cognition by indicating the epistemological basis of the concept of sustainable development. It will endeavor to draw attention to the need of shaping the attitude of the knowing subject, to facilitate adequate understanding of what we commonly address as sustainability and implementing the proposals of sustainable development and verification of the related sources of cognition.